2021
DOI: 10.1007/s10143-021-01515-3
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and rupture risk of intracranial aneurysms—a systematic review

Abstract: Dyslipidemia is a well-established risk factor for coronary artery disease. However, the effect on cerebral artery disease, and more specifically the rupture risk of intracranial aneurysms, is unclear and has not yet been reviewed. We therefore performed a systematic review to investigate associations between different types of dyslipidemia and incidence of aneurysmal subarachnoid hemorrhage (aSAH). We used the MEDLINE, Embase, and Web of Science databases to identify clinical trials that compared the rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This result supports previous studies into the inverse association between hyperlipidemia and aneurysm rupture. 32,33 Particularly, the effect was more profound for hyperlipidemia treated with antihyperlipidemic agents. Similarly, growing evidence from experimental animal models and retrospective clinical studies supported the concept that the inverse association is more dependent on the use of antihyperlipidemic agents as statins have vascular protective effects by antioxidative stress and anti-inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This result supports previous studies into the inverse association between hyperlipidemia and aneurysm rupture. 32,33 Particularly, the effect was more profound for hyperlipidemia treated with antihyperlipidemic agents. Similarly, growing evidence from experimental animal models and retrospective clinical studies supported the concept that the inverse association is more dependent on the use of antihyperlipidemic agents as statins have vascular protective effects by antioxidative stress and anti-inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In MLR, diabetes mellitus, dyslipidemia ( 19 ), ischemic stroke history, hemorrhagic stroke history and age stratification for those aged 60–69 years were all independent protective factors. This is consistent with the results of Olivia Rousseau and his colleagues working on the ICAN project study in the UK 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be because most patients with hypertension undergo antihypertensive treatment and tend to have normal blood pressure after antihypertensive treatment; antihypertensive drugs may further prevent aneurysm rupture through other mechanisms ( 22 ). A recent review study including five case–control studies found that hypercholesterolemia is associated with a lower rupture risk of IAs ( 23 ). By contrast, in this study, an inverse relationship was observed; hypercholesterolemia increased the risk of aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Statin therapy has been increasingly used not only for lowering blood lipid levels but also for treating cardiovascular and cerebrovascular diseases. Patients with hypercholesterolemia may gain a protective benefit for aneurysm rupture from statin use ( 23 ). Further studies with rigorous inclusion and exclusion criteria should be conducted to determine these associations.…”
Section: Discussionmentioning
confidence: 99%